(untitled) (Lex localis - Journal of Local Self-Government, 2024)
The objective of the research was to assess the "Comparative Effects of Circuit Resistance Training and Aerobic Circuit Resistance Training on Speed and Speed Endurance of Early Adult Female Volleyball Players (20-25 Years)." We randomly picked 63 female volleyball players and then split them into three groups of equal size. Participants in Group 1 underwent circuit resistance training (CRT), those in Group 2 engaged in aerobic circuit resistance training (ACRT), and individuals in Group 3 were allowed to take part in their standard volleyball practice without any supplementary training regimen. This study concentrated on velocity and endurance of velocity as the primary dependent variables. The 30-meter sprint test was used to test speed both before and after the eight-week training session. The repeated shuttle run test was used to examine speed endurance. Both tests were conducted to assess the degree of speed endurance. We used an analysis of covariance, also known as an ANCOVA, to find out if there were any big differences between the three groups. The research demonstrated that both CRT and ACRT significantly enhanced speed and speed endurance compared to the control group. People in the CRT group showed better explosive speed, while people in the ACRT group showed better speed endurance. The results show that both CRT and ACRT help early adult female volleyball players do better on speed-related performance tests. This gives trainers a framework for creating training plans that are based on research. Some of the words that go with this article are "circuit resistance training," "aerobic circuit resistance training," "speed," "speed endurance," "female volleyball players," and "ANCOVA."